The Impact of Transformational Leadership Style on Employee Engagement - Cynthia Wibowo; Elyzabeth Wijaya; Agus Susanto; Susanto Susanto (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
It is important that companies attract and retain employees. The human resource is important for company in achieving the goal. Employees who feel engaged have high levels of involvement and satisfaction. The employees are said to be engaged when they have passion, commitment and the willingness to expend their effort to help the employer in achieving the goals. One of the ways to keep employee productivity is through employee engagement. The organizational effectiveness will be realized if the employees who perform assigned duties are willing to engage in activities. The leader should make employees feel comfortable in doing the job. Research design used in this research is descriptive research design and correlational research design. Research methods which used are descriptive statistic analysis, validity and reliability test, normality test, coefficient correlation, coefficient of determinant, simple linear regression analysis and Z testing. The conclusion of this research is there is impact transformational leadership style towards employee engagement. The conclusion is proved with Z test. The calculation of Z test shows that Zcount (10.13) is higher than Ztable (1.96). The alternative hypothesis is accepted and null hypothesis is rejected. Coefficient of correlation is 0.896. It shows that there is strong and positive relationship between variables. Coefficient of determination is 80.3%. It shows that employee engagement can be explained by transformational leadership style in 80.3% while the remaining in 19.7% can be explained by other factors.